2006
DOI: 10.1007/s10530-006-9020-x
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm invasions of ecosystems devoid of earthworms: effects on soil microbes

Abstract: Recent studies document NorthAmerican earthworm invasions and their profound effects on the structure of the soil profile, which is the habitat for soil microorganisms (mainly fungi and bacteria). Dramatic alterations made to these layers during earthworm invasion significantly change microbial community structure and therefore microbial activities such as C transformations. Understanding the impacts of earthworm invasion on the microbes themselves will give insight into earthworm effects on microbial activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 68 publications
(159 reference statements)
4
51
0
Order By: Relevance
“…There have been few studies on the interaction between earthworms and mycorrhizae, and most have focussed on arbuscular mycorrhizae (McLean et al 2006). Given the overwhelming importance of ectomycorrhizae in coniferous forests and their distribution within the organic layers (e.g., Goodman and Trofymow 1998), there is an urgent need to determine if and how invasive earthworms will jeopardize this vital association between coniferous trees and their fungal partners.…”
Section: Earthworms and Mycorrhizaementioning
confidence: 99%
“…There have been few studies on the interaction between earthworms and mycorrhizae, and most have focussed on arbuscular mycorrhizae (McLean et al 2006). Given the overwhelming importance of ectomycorrhizae in coniferous forests and their distribution within the organic layers (e.g., Goodman and Trofymow 1998), there is an urgent need to determine if and how invasive earthworms will jeopardize this vital association between coniferous trees and their fungal partners.…”
Section: Earthworms and Mycorrhizaementioning
confidence: 99%
“…A correlation crossproducts matrix, which produces correlation coefficients among the compounds, was used in the PCA. This method provides a broken stick eigenvalue; the broken-stick eigenvalue was less than the actual eigenvalue for the first and second axes; therefore these were used for interpretation (McCune and Mefford 1999). Pearson and Kendall correlations with the main matrix were calculated in PC-ORD.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Li et al 2002) soil microbial biomass and activity. Reviewing the previous literature on exotic earthworm effects on soil microbes, McLean et al (2006) concluded that earthworms change microbial community composition towards a smaller, but more active microbial community. They moreover hypothesized that impacts of exotic earthworms on soil microbes depend on the stage of invasion: initial decreases in soil microbial respiration and metabolic quotient may be followed by a decrease in microbial C use efficiency.…”
Section: Introductionmentioning
confidence: 99%